2013
DOI: 10.1017/jsc.2013.8
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Nondaily Smoking among Young Adults: Scale Development and Validation

Abstract: Introduction: Given the increased rates of nondaily smoking and the lack of validated measures to assess factors related to nondaily smoking, we aimed to develop a measure of reasons for nondaily smoking among young adults. Specifically, we developed a scale assessing reasons or triggers for nondaily smoking and examined its reliability, factor structure, and concurrent validity. Methods: We administered an online survey to 2,000 students at six colleges in the Southeastern US, and 718 (35.9%) returned a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The study was cross-sectional, precluding examination of the impact of expectancies on ANTP initiation or progression, or the temporal relationship between ANTP and cigarette use. It is possible the sample was unrepresentative of young adult non-daily smokers due to the recruitment approach, although it was comparable to recent studies in terms of cigarette consumption (Berg, 2014; Schauer, et al, 2014). Finally, because it was not assessed, the extent to which participants used ANTPs labeled as low- or non-nicotine is unknown.…”
Section: Discussionmentioning
confidence: 55%
“…The study was cross-sectional, precluding examination of the impact of expectancies on ANTP initiation or progression, or the temporal relationship between ANTP and cigarette use. It is possible the sample was unrepresentative of young adult non-daily smokers due to the recruitment approach, although it was comparable to recent studies in terms of cigarette consumption (Berg, 2014; Schauer, et al, 2014). Finally, because it was not assessed, the extent to which participants used ANTPs labeled as low- or non-nicotine is unknown.…”
Section: Discussionmentioning
confidence: 55%
“…[41][42][43][44] A prior study suggested that non-daily smokers were less likely than daily smokers to report smoking to relieve negative states 45 while reporting negative affect regulation as a reason for non-daily smoking was associated with greater past-two week depressive symptoms among college students. 46 More research is needed to understand the mechanisms, including affect-regulation processes, underlying the depression-smoking relationship in general and specifically for non-daily smokers. The association between depression and non-daily smoking further suggests a need to learn more about how depression impacts quit outcomes for non-daily smokers since depression has been linked to lower abstinence success in the general smoking population.…”
Section: Key Results and Interpretationmentioning
confidence: 99%
“…Although our results do not imply that the direction of the relationship and mechanisms supporting the relationship between NDS and mental health is not well established, some hypotheses are supporting the relationship. Berg suggested that negative affect regulations of non-daily smokers were associated with greater depressive symptoms among college students [ 47 ]. It has been also proposed that nicotine may have direct distress relief effects that do not depend on withdrawal-relief, but actually reduce distress from exogenous sources such as depressive symptoms [ 43 ].…”
Section: Discussionmentioning
confidence: 99%